The astronomical seeing measurements at Langkawi National Observatory - Ahmad, Nazhatulshima; Chin, Wei Loon; Syukor, Muhammad Shamin; Haron, Saedah; Zainuddin, Mohd. Zambri; Md Tahar, Muhammad Redzuan (IEEE, 2015)
We present seeing measurements of Langkawi National Observatory during the period from 2014 May 6 to 2015 March 26. The measurements were carried out with Differential Image Motion Monitor (DIMM) of STV and Alcor system. The median seeing was measured to be best at 0.8 arcseconds in May 2014 with STV system and 0.5 arcseconds in December 2015 with Alcor system.